Optimalisasi tumbuh kembang anak berkebutuhan ‎khusus: Terapi bermain di Yayasan Matahari Banyuwangi ‎Jawa Timur - Amelia, Vika (Maliki Interdisciplinary Journal, 2023)
The life of child with special needed in Indonesia is still classified as being very neglected. The development of ABK is a gradual growth and expansion, starting from simple things to more complex things. Because at this time basic growth will influence and determine the next child's development. Therapy by playing cooperatively can develop their ability to socialize without leaving their world, namely the world of play. This research is descriptive qualitative in nature with the aim of knowing and analyzing play therapy with growth and development in children and its impact on the growth and development of children with special needs at the Matahari Banyuwangi Foundation, East Java. This research was conducted during the KKM (Student Work Class) activities from December to January. The data obtained is the result of direct observation during the community service work program.